(untitled) (Fiep Bulletin - online, 2014)
The ability of sliding forward is the first movement one should learn and perform in order to develop the different movements and peculiar rules of the distinct skating modalities. For the successful teaching-learning process of this ability, knowing the characteristics of this skill, among other factors, is very important because it provides parameters for its evaluation. Thus, the objective of this work was to construct a matrix for the analysis of the basic characteristics of sliding forward on a roller skate. In the first stage, a descriptive model of the ability of sliding forward based on observations of the movement through videos and skating championships was built. The descriptions were structured and divided into: execution phase I, which considered the moment still and the leg impulsion movement plus the behavior of the body parts in separated; execution phase II, which observed the sliding leg (ground) and execution phase III, which considered the moment of the second impulse with leg exchange. After this stage, Physical Education and Skating professors performed reviews and corrections of the descriptions in order to be the clearest as possible. The material containing the descriptions was sent to skating professors of the state of Rio Grande do Sul with the objective of verifying and performing considerations on the descriptions elaborated. All professors agreed with the descriptions and listed the most common errors during the execution of each phase, thus enabling the formulation of the matrix for the analysis of the sliding movement. The model resulting from this study is presented as a first version that will enable evaluations and hence will favour interventions on the sliding ability teaching-learning pedagogical process.